Recalibrating Copyright Law? A Comment on the Supreme Court of Canada's Decision in CCH v. Law Society of Upper Canada - Scassa, Teresa (Université d'Ottawa | University of Ottawa, 2004)
The Supreme Court of Canada’s unanimous decision in CCH Canadian Ltd. et. al. v. Law Society of Upper Canada has major implications for the development of copyright law in Canada. This paper offers a critical examination of the Court’s decision, with a focus on the new standard of originality established by the Court, the Court’s approach to the “authorization” of infringing acts, and the new interpretive approach to fair dealing. The author argues that the case signals a new direction in copyright law in Canada – one that places real limits on the scope of the rights of owners of copyright.
Keywords: originality; fair dealing; copyright law